Distance Learning For Military Doctors in Crisis Situations: The DILEMMA Cross-Sectional Study Results - Sydorova, Nataliia; Savytskyi, Valerii; Kuts, Taras (Acta Paedagogica Vilnensia, 2024)
Distance learning for medical personnel, although convenient in times of crisis (pandemics, military operations), can be a problem in terms of the limited practical component of such training. The goal of presented Survey on DIstance LEarning for students of the Ukrainian Military Medical Academy (DILEMMA) was to optimize the educational process for doctors studying at the Ukrainian Military Medical Academy (UMMA) based on the results of students’ survey dedicated to implemented forms of online teaching. Methods: The data presented reflect the results of 147 trainees’ survey dedicated to their satisfaction and ways to improve distance learning component of training/retraining at UMMA during such crisis situations as pandemics and hostilities. Primary and secondary endpoints were analyzed for groups of interns (DILEMMA-1, n=78) and physicians with practical experience participating in postgraduate activities at UMMA (DILEMMA-2, n=69). Results. The overall evaluations of distance learning as measured by a 10-point scale (primary endpoint) were 5.9±3.3 for DILEMMA-1 and 6.5±3.3 for DILEMMA-2 (p=0.27), which indicates a moderate overall evaluation. The proportion of satisfied and very satisfied students was smaller in the DILEMMA-1 group compared to DILEMMA-2 but remained quite high (76.9% vs. 92.8%, respectively, p<0.05). Respondents of the DILEMMA-1 and DILEMMA-2 arms gave different answers to the questions related to their preferred forms of online education, mode, and schedule. In particular, representatives of the DILEMMA-2 arm mostly prefer to have their online classes after 3:00 p.m. (67.5%) with duration for about 2 hours (56.5%), while most participants in DILEMMA-1 arm (73.1%) choose time interval from 9:00 a.m. to 11:00 a.m. and 62.8% consider the optimal duration to be 3–4 hours of online classes per day. According to results of survey, optimization of distance learning component was made at UMMA. Conclusions. Differences in the perception of distance learning between interns and doctors with practical experience necessitate a differentiated approach to the implementation of distance learning for these groups of students. In addition, the special categories of respondents among students were identified by us, which lead to the destructuring of the response matrix and the nonparametric nature of some data, dictate the need to censor extremely negative (“denialists”) and extremely positive (“pleasers”) respondents when assessing the quality of teaching by anonymous survey of students, and therefore the size of the initial sample depending on contingent should be increased by 16–25%.